Personality Traits and Memory: A Multilevel Analysis Across 27 Countries From the Survey of Health, Ageing and Retirement in Europe. (July 2021) - Luchetti, Martina; Terracciano, Antonio; Stephan, Yannick; Aschwanden, Damaris; Sutin, Angelina R.
Personality traits are associated with memory in older adulthood: Individuals higher in conscientiousness and openness and lower in neuroticism tend to perform better on memory-recall tasks. We conducted a preregistered study to replicate these associations in a large, multinational cohort and test whether the associations varied by national-level socioeconomic indicators (e.g., per capita gross domestic product). Multilevel modeling was used to analyze data from 71, 566 individuals (age: M = 67.9 years, SD = 9.5; 57% women) across 26 European countries and Israel. Higher conscientiousness, openness, and extraversion and lower neuroticism were associated with better memory performance, even when analyses accounted for risk factors including diabetes, hypertension, obesity, emotional disorders, and sleeping problems. Consistent with the resource-substitution hypothesis, results showed that higher conscientiousness and agreeableness and lower neuroticism were associated with better memory in countries with lower gross domestic product. This pattern suggests that psychological (trait) resources may help compensate for country-specific disadvantaged contexts.